2018
DOI: 10.3892/ol.2018.9498
|View full text |Cite
|
Sign up to set email alerts
|

High expression of GALNT7 promotes invasion and proliferation of glioma cells

Abstract: Polypeptide-N-acetyl-galactosaminlytransferase 7 (GALNT7), a member of the GalNAc-transferase family, has not been previously evaluated as a prognostic factor of glioblastoma (GBM) or low-grade glioma (LGG). Based on The Cancer Genome Atlas database and bioinformatics analyses, the expression of GALNT7 was demosntrated to be higher in GBM and LGG tissues than in normal brain tissue. The expression levels of GANLT7 were associated with age, tumor grade, survival rate, disease-free survival time and overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Owing to rapid proliferation, metastasis and angiogenesis, this disease is relatively hard to treat (17,18). The prognosis of patients with glioma is relatively poor due to metastasis and recurrence (3,19). The incidence and mortality rates of glioma are continuously increasing (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to rapid proliferation, metastasis and angiogenesis, this disease is relatively hard to treat (17,18). The prognosis of patients with glioma is relatively poor due to metastasis and recurrence (3,19). The incidence and mortality rates of glioma are continuously increasing (1).…”
Section: Discussionmentioning
confidence: 99%
“…Glioma is an aggressive brain cancer with high morbidity and mortality rates (1) characterized by aggressive proliferation, invasion and dismal prognosis (2). Although great progress has been made in the therapeutic field, the prognosis of patients with glioma remains poor (3). Recent studies have revealed a number of aberrantly expressed genes, which may be involved in the progression of glioma (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Other potentially relevant genes displaying the same expression trend were the heparan sulphate proteoglycan GPC2 (a marker of immature neurons 62,63 ), the helix-loop-helix transcription factor ID4 (a marker of postmitotic neurons 64 ), and the signaling molecule FGFR3 that has been implicated in epilepsy 65 . Genes downregulated in KO cells and upregulated in rescue cells included urokinase-type plasminogen activator PLAU (deficiency in mouse models increases seizure susceptibility 66 ), the glycoprotein GALNT7 (upregulation of which has been found to promote glioma cell invasion 67 ) and the brain tumor gene MYBL1 (that has been shown to be regulated by O -linked N -acetylglucosamine 68 . Similar expression changes were observed in NSCs differentiated from induced pluripotent stem cells (iPSCs) that we had generated from family 1 ( Supplementary Figure 6) .…”
Section: Resultsmentioning
confidence: 99%
“…For example, CSGALNACT1 is implicated mostly in prostate cancer, but also serves as a prognostic biomarker in multiple myeloma (Qi et al 2020). GALNT7 is favorable as a prognostic biomarker in colorectal cancer and gliomas, but has unfavorable results in pancreatic cancer with a lower survival rate [https://www.proteinatlas.org] (Uhlen et al 2015; Hua et al 2018). STT3A has also been recognized as a diagnostic panel biomarker for thyroid cancer, and ALG10 autoantibodies have been implicated as potential diagnostic biomarkers for breast cancer, consistent with the data in EDRN (Zhong et al 2008).…”
Section: Discussionmentioning
confidence: 99%